Producción y realización del manual de identidad visual de _NIM” - Zegarra Mallma, Pablo Eduardo (2020)
This project consists in the realization of a brand guidelines for _NIM, a peruvian gender-neutral clothing brand (clothes not specifically addressed to either the male or female audience, but to both). The purpose of carrying out this project was to design a guide that brings together the brand's strategic concepts and vision. We seek that they function as a main guide in the production of all kinds of visual communication elements related to the brand. The design procedure included constant advice from design experts, feedback from clients in each phase of the manual design process and constant learning about the key points in the production of an identity manual like review of materials such as tutorials, online courses on visual identity and analyzing what the competition does. The main attributes of this project are that it effectively manages to implement the brand's strategic concepts as pillars and integrates axes of the brand guidelines. In that way, we create a document that is as functional as it is creative and that serves to maintain coherence in _NIM communications, enhancing their differentiation. and guiding designers, communicators or companies that work with the brand in the future.